The Case for Emancipatory Ecospirituality - Barniaudy, Clément; Delorme, Damien (The Trumpeter)

(untitled) (Athabasca University Press, 2024)
Scientific consensus on the environmental emergency has prompted recognition that business as usual is not only materially catastrophic but ethically, socially, and politically unfair. Working from different axiological perspectives, scholars in the environmental humanities have framed the crisis as an opportunity for paradigmatic and radical change, encouraging a new “Great Transformation” or “Great Transition”. Such appeals tend to focus on systemic change at economic and political levels. Nevertheless, the ecological crises as a revolutionary opportunity demands an integral metamorphosis of Western capitalist cultures, including the ontological and ethical dimensions embedded in perception, desires, and affects, and grounded in elementary subjective practices. In this light, ecospirituality is integral to transformative ecology. Confronted with the ecological crisis, this calls for us to set to work on the widely discussed issue of the relations between spirituality and politics.